PANDANGAN ISLAM TERHADAP METABOLISME PROTEIN - Sari Dianti; Anggi Suwi Apriansyah; Rapies Honal Hari Sya'ban; Qomariah Hasanah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Islam obliges its followers to seek knowledge, where in the book of the Qur'an there is all knowledge from the smallest to the largest including knowledge related to living things in which it describes protein metabolism. The purpose of this study was to determine the Islamic view of protein metabolism. The author uses qualitative methods with sources in the form of books, journals, al-Qur'an, al-Hadith and sources from theses and articles from the internet. The results of the study show that metabolism is one of the most important processes in the body of living things, in order to produce the energy needed for survival. One example of metabolism is protein metabolism, which is a chemical and physical process that occurs in two phases, namely anabolism and catabolism where the change (anabolism) of proteins into amino acids and the breakdown (catabolism) of amino acids in proteins. A high source of protein that is needed by the body comes from animal protein as contained in QS. An-Nahl verse 5. In order to maintain protein metabolism, food must be in accordance with the portion. Therefore, Islam regulates food that is halal and good for processing in the body, including the quantity of food that is consumed. This was exemplified by the Prophet by putting food into the mouth in small portions to help digestion go well.